Recommendations in credence goods markets with horizontal product differentiation - Momsen, Katharina (Journal of economic behavior & organization, 2021)
I experimentally analyze whether the introduction of watchdogs and the revelation of sellers’ investment decisions can improve the market outcome in credence goods markets with horizontal product differentiation. Sellers can always give advice, yet they only observe consumers’ valuations if they invest. I find that in the absence of watchdogs and with concealed investment decisions, both prices and investment rates are low and sellers give selfish advice. Each measure alone is not sufficient to improve recommendations; only the joint introduction has a significant positive impact on both quality and frequency of recommendations, but leaves welfare unaffected.